To find the outputs for the function \( f(x) = - (x + 1)^2 + 4 \) for the given inputs, we will evaluate the function at each input value provided.
-
For \( x = -1 \): \[ f(-1) = -((-1) + 1)^2 + 4 = -(0)^2 + 4 = 0 + 4 = 4 \]
-
For \( x = 0 \): \[ f(0) = -((0) + 1)^2 + 4 = -(1)^2 + 4 = -1 + 4 = 3 \]
-
For \( x = 1 \): \[ f(1) = -((1) + 1)^2 + 4 = -(2)^2 + 4 = -4 + 4 = 0 \]
-
For \( x = 2 \): \[ f(2) = -((2) + 1)^2 + 4 = -(3)^2 + 4 = -9 + 4 = -5 \]
Now we can summarize the outputs in a table:
\[ \begin{array}{|c|c|} \hline x & f(x) \ \hline -1 & 4 \ 0 & 3 \ 1 & 0 \ 2 & -5 \ \hline \end{array} \]
The values of \( f(x) \) are:
- \( f(-1) = 4 \)
- \( f(0) = 3 \)
- \( f(1) = 0 \)
- \( f(2) = -5 \)
From this table, the largest output occurs at \( x = -1 \), where \( f(-1) = 4 \).
Therefore, the answer is: \( x = -1 \).